2021
DOI: 10.3389/fpsyg.2021.769732
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual Interaction in Digital Contexts and Its Implications for Sexual Health: A Conceptual Analysis

Abstract: Based on its prevalence, there is an urgent need to better understand the mechanisms, opportunities and risks of sexual interaction in digital contexts (SIDC) that are related with sexual arousal. While there is a growing body of literature on SIDC, there is also a lack of conceptual clarity and classification. Therefore, based on a conceptual analysis, we propose to distinguish between sexual interaction (1) through, (2) via, and (3) with digital technologies. (1) Sexual interactions through digital technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 163 publications
(194 reference statements)
0
5
0
4
Order By: Relevance
“…B. Döring et al 2021 ; Naezer und van Oosterhout 2021 ) dokumentiert sich, dass beide Gruppen Victim Blaming praktizieren, indem sie die Verantwortung für sexuelle Grenzverletzungen mittels digitaler Medien bei den betroffenen Bildproduzentinnen verorten. Dies kann implizit durch eine vermeintlich verstehende Haltung geschehen, die nach Gründen für die Handlungen der Bildproduzent*innen sucht und diese in der vermeintlichen Abhängigkeit der Person, die Sexting betreibt, von anderen findet.…”
Section: Fazitunclassified
See 1 more Smart Citation
“…B. Döring et al 2021 ; Naezer und van Oosterhout 2021 ) dokumentiert sich, dass beide Gruppen Victim Blaming praktizieren, indem sie die Verantwortung für sexuelle Grenzverletzungen mittels digitaler Medien bei den betroffenen Bildproduzentinnen verorten. Dies kann implizit durch eine vermeintlich verstehende Haltung geschehen, die nach Gründen für die Handlungen der Bildproduzent*innen sucht und diese in der vermeintlichen Abhängigkeit der Person, die Sexting betreibt, von anderen findet.…”
Section: Fazitunclassified
“…Neuere Begriffe wie „bildbasierte sexuelle Gewalt“ (engl. image-based abuse ) weisen auf ein breiteres Verständnis des Problems und die Tatsache hin, dass das Veröffentlichen der Bilder über die Rache von Ex-Partnern hinaus auch heimlich produzierte Bildaufnahmen (wie das sogenannte Upskirting , Downblousing ) sowie Material umfasst, das gehackt oder auf andere Weise gestohlen wurde, bevor es über Soziale Medien geteilt wurde ( Döring et al 2021 ; Stokes 2014 ). Als eine weitere Form bildbasierter sexueller Gewalt gilt Sextortion , was die Drohung beschreibt, ein sexuelles Bild zu veröffentlichen, um die Abgebildeten zu erpressen ( Wolak et al 2018 ).…”
unclassified
“…A further affordance of VR technology not covered in previous research is the use of teledildonics. Teledildonics allow for a sexual experience with other people at a distance by creating an interface between the two (or more) people that stimulates sexual pleasure either synchronously or for one party [33]. The concept of teledildonics first emerged in the 1990s but has become more prevalent with the emergence of VR as a consumer medium [34,35].…”
Section: Teledildonicsmentioning
confidence: 99%
“…The concept of teledildonics first emerged in the 1990s but has become more prevalent with the emergence of VR as a consumer medium [34,35]. Research has indicated that technologically mediated sexual interactions have the potential to improve sexual wellbeing in some populations [33,36] Teledildonic devices, such as remotely controlled dildos, provide tactile sensations that simulate part of a subject's body on the behest of another person while connected digitally, enabling a subject to interact with a second subject as if they were in the same place at the same time. This can create a feeling of 'being there' through sensory biofeedback as well and auditory and visual immersion [1,35].…”
Section: Teledildonicsmentioning
confidence: 99%
“…As already addressed, technologies can play a role in mediating erotic communication, but also serve as interaction partners themselves. Consistent with Döring et al (2021) , technologies can be incorporated into sexualized interactions in three different ways; first, they can enable sexualized interactions by connecting people (e.g., online dating platforms). Second, technologies can mediate sexualized interactions (e.g., webcam sex), and finally, people can have a sexualized interaction with the technology itself (e.g., with sexualized chatbots or robots).…”
Section: Theoretical Overviewmentioning
confidence: 99%